Pengaruh Cara Pemrosesan Resin AkrilikTerhadap Sifat Fisik Dan Mekanik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Acrylic resin processing becomes an important factor for comfortable, blocompatlble, aesthetic, and economical denture. The aim of this research is to determine the effect of acrylic resin processing toward its physical and mechanical properties. This research examined two acrylic resin processing methods, namely stove method (time and temperature are uncontrolled) and curing unit method (time and temperature are controlled). The physical and mechanical properties of acrylic resin processed by the two methods were examined according to the ADA (American Dental Association) specification number 12. The result showed that there were not any different properties of acrylic resin processed by the two methods on: surface characteristic, polished surface, translucency, porosity, and color stabilization. Acrylic resin processed by curing unit showed brighter and clearer in color than the stove one. The transverse strength of acrylic resin processed by curing unit was higher and showed significant difference to the stove one (p< 0.05). In conclusion, acrylic resin processed by curing unit method produced the same physical properties, but had higher mechanical and aesthetic properties than the stove one Key words: acrylic resin processing, physical properties, mechanical properties